2019
DOI: 10.1007/s12275-020-9384-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of a neutralization assay based on the pseudotyped chikungunya virus of a Korean isolate

Abstract: Development of a neutralization assay based on the pseudotyped chikungunya virus of a Korean isolateThe Chikungunya virus (CHIKV) belongs to the Alphavirus genus of Togaviridae family and contains a positive-sense single stranded RNA genome. Infection by this virus mainly causes sudden high fever, rashes, headache, and severe joint pain that can last for several months or years. CHIKV, a mosquito-borne arbovirus, is considered a re-emerging pathogen that has become one of the most pressing global health concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…This might be confirmed by the detection of the presence of IgG antibodies in patients [ 28 , 29 ]. PRNT is used to measure the titer of neutralizing antibodies in the serum by counting the number of plaques of viral infection [ 33 ]. This test has been used conventionally in laboratories for vaccine efficacy that requires the hazardous live CHIKV, and requires fewer days to complete when compared to the RDT [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be confirmed by the detection of the presence of IgG antibodies in patients [ 28 , 29 ]. PRNT is used to measure the titer of neutralizing antibodies in the serum by counting the number of plaques of viral infection [ 33 ]. This test has been used conventionally in laboratories for vaccine efficacy that requires the hazardous live CHIKV, and requires fewer days to complete when compared to the RDT [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…PRNT is used to measure the titer of neutralizing antibodies in the serum by counting the number of plaques of viral infection [ 33 ]. This test has been used conventionally in laboratories for vaccine efficacy that requires the hazardous live CHIKV, and requires fewer days to complete when compared to the RDT [ 33 , 34 ]. Currently, neutralization assays, such as the non-infectious virus replicon particles and pseudotyped viruses, have been developed [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, measurement of luciferase activity is complicate and expensive. Dual reporters (ZsGreen1 and luciferase) have been increasingly engineered into PsV of this study and other reports 27 , 28 . The fluorescent reporter ZsGreen1 in PsV can be used to monitor efficiency of transfection and titration, which is more convenient and cheaper than the reporter luciferase.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, visualization and counting of plaques in PRNT are time-consuming and laborious procedures. Many studies have demonstrated that the PsV neutralization test could be a good substitute for the plaque reduction test 27 , 34 . In order to overcome the limitations of PRNT mentioned above, here we developed a PsV neutralization assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation